INVOLVEMENT OF JOB SATISFACTION AS A MEDIATOR OF WORK MOTIVATION ON TEACHER PERFORMANCE - Pratikno Pratikno; Sutianingsih Sutianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
A teacher's work is demonstrated by how well they do it. One way to achieve educational goals is for teachers to carry out their duties well. This research aims to determine how work motivation and happiness influence how well teachers do their work. This research is a quantitative study with teacher performance (y), work motivation (X1), and job satisfaction (X2). The population in this study were all teachers and employees of SMP Negeri 2 Banyudono. The data in this study consisted of primary and secondary data collected using questionnaires, documentation, and literature, which were analyzed using descriptive and inferential statistics. The results obtained are that work motivation and job satisfaction affect teacher performance. Keywords: job satisfaction, motivation, performance